Dynamics of Intellectual Confidence in Problem Solving - Marina I. Kunashenko; Anna A. Matyushkina (Lomonosov Moscow State University, 2023)
Background. The problem of criteria for evaluating solution success is one of the most important for psychology of creative thinking. Evaluation of the solution by the subject during the process of thinking in the form of «confidence / doubt» can be criteria and basis for subject's experiencing potential success or failure, which leads to continuation or stop in solving. The objective. The study was to research the dynamics of intellectual confidence / doubt at different stages of problem-solving process. Sample. The study involved 66 university students, specialists and non- specialists in relation to the content of the tasks. Methods. The subjects solved 8 problematic tasks of scientific and artistic content with hints and estimate interest and confidence at different stages of solving with subjective scales. The following methods were used for intellectual characteristics: "Raven's Progressive Matrices", "Complex Analogies". Results. 6 types of dynamics of intellectual confidence were identified, which correlated in various ways with the success of the solution. Successful solution of problematic scientific situations for specialists is associated with confidence at every stage, for non-specialists it is associated with doubts at the stages of understanding the problem and the formulation of solution. For problematic situations of artistic content solved by non-specialist, the following types of dynamics are associated with successful solution: «doubt - doubt - confidence», «confidence at all stages»; the latter was also observed with an unsuccessful solution. For this reason 2 types of confidence were identified: (1) reasonable, based on hints, leading to a successful solution, and (2) non- reasonable, without relying on a hint, not leading to a successful solution. Conclusion. The procedural criteria to evaluate solution are the intellectual emotions of confidence or doubt that regulate the process of thinking. Depending on the stage of solution and the content of the task, intellectual confidence changes in different ways for specialists and non-specialists, performing the function of a preliminary assessment and regulation of solving process.